STATE OF DEVELOPMENT OF LABOR RELATIONS IN SMALL BUSINESS AND ENTREPRENEURSHIP IN JIZZAKH REGION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article stipulates that the organization of labor in entrepreneurial activity is inextricably linked not only with the specific characteristics of the entity engaged in one or another type of economic activity, but also with the characteristics of the stage of development of the national economy. Priority tasks have been identified for the further development of small and private entrepreneurship in the context of deepening the training of workers of small enterprises in effective labor methods, transition to rational methods of using labor potential, promoting advanced labor methods, and reducing costs through the introduction of the listed work methods.
Keywords: small business and private entrepreneurship, labor, labor relations, labor organization, labor standards, incentives.